PENENTUAN KONDISI KESEIMBANGAN UNIT LEACHING PADA PRODUKSI EUGENOL DARI DAUN CENGKEH - Tagora Bangkit P.S; Rinaldry Sirait; Iriany (Jurnal Teknik Kimia USU, 2012)
Leafs of clove is an alternative source to obtain clove oil. Clove oil is classified into essential oil with eugenol as its main component. Clove oil is widely used in pharmaceutical, food and beverage industries. The objective of this research is to obtain clove oil by solid-liquid extraction (leaching). This research was expected to give data of solid-liquid equilibrium for designing solid liquid extractor. This research was carried out by leaching process with ethanol as its solvent. The extract was then purified by distillation to separate solvent from oil. The fixed variables which were used in this research were stirring rate of 460 rpm and 90 grams dry-based clove leaf. Extraction process was carried out by using solvent with temperature of 30oC and 50oC, extraction time of 1-3 hours with 0.5 hour increment and solvent volume of 500 ml and 600 ml. The results showed that the highest yield of clove oil extraction was obtained at temperature of 50oC and solvent volume of 600 ml. Equilibrium was reached after 2.5 hours and 79% eugenol concentration in the solvent.